Nanoreinforcement mechanism of organomodified layered silicates in EPDM/CIIR blends: experimental analysis and theoretical perspectives of static mechanical and viscoelastic behavior. Issue 1 (2nd January 2021) - Ashok, Neelesh; Balachandran, Meera; Das, Narayan Chandra; Remanan, Sanjay
ABSTRACT: Ethylene propylene diene (EPDM)–chlorobutyl rubber (CIIR) blends can withstand both radiation and hydrocarbon environments and are used for elastomeric components in nuclear plants. This work investigates the influence of organomodified layered silicates (OMLS) on the mechanical and viscoelastic properties of EPDM–CIIR blends. The morphology and physicochemical interactions are evaluated by X-ray diffraction, transmission electron microscopy and Fourier transform infrared spectroscopy and correlated with the enhancement in mechanical properties. Mooney–Rivlin plots provided insight into the nonlinear mechanical behavior of EPDM–CIIR nanocomposites. From a dynamic mechanical analysis (DMA), it was found that blends with 5 phr OMLS content had the maximum storage modulus. Significant lowering as well as broadening of tanδ peak was observed for blends with well-dispersed OMLS (5 phr). The entanglement density and constrained volume near the interfaces, calculated from the DMA data, gave an insight to the reinforcing mechanism. Rheological characteristics of the nanoreinforced blends also revealed the stiffening effect of OMLS. Payne effect and stress relaxation studies confirmed good rubber–OMLS interactions. The applicability of various analytical models to predict the static and dynamic modulus as well as the Payne effect is explored. Graphics Abstract: uf0001